Effect of Intravenous Dexmedetomidine on Intraocular Pressure in Patients Undergoing Glaucoma Surgery Under Local Anesthesia: A Pilot Study. Issue 10 (October 2020) - Senthil, Sirisha; Burugupally, Keerthi; Rout, Umashankar; Rao, Harsha L.; Krishnamurthy, Rashmi; Badakere, Swathi; Choudhari, Nikhil; Garudadri, Chandrasekhar
Abstract : Precis: Preoperative intravenous (IV) dexmedetomidine produced a 33% reduction in intraocular pressure (IOP) within 15 minutes of administration in patients with glaucoma. Purpose: To evaluate the effect of preoperative IV dexmedetomidine on IOP in adult patients undergoing glaucoma surgery under local anesthesia. Methods: In a prospective interventional case series, 12 patients with uncontrolled IOP (IOP>24 mm Hg in both the eyes) with the systemic status of American Society of Anesthesiologists (ASA) classification I-II, received IV dexmedetomidine 0.6 µg/kg 30 minutes preoperatively. The IOP of the nonsurgical eye (measured with Perkins tonometer), the heart rate (HR), and blood pressure (BP) were recorded 5 minutes prior, 15 minutes and 2 hours after IV dexmedetomidine administration, and were compared using analysis of variance and Tukey honestly significant difference tests. Results: There were 4 women and 8 men with a mean age (±SD) of 60.6±10.4 years. The mean number of antiglaucoma medications was 4.3±1.3. The mean pre-dexmedetomidine IOP was 31.5±5.6 mm Hg. At 15 minutes post-dexmedetomidine administration, the mean and percentage drop in IOP were 10.2±3.2 mm Hg ( P =0.001) and 33%±11%, respectively. The mean and percentage drop in systolic BP were 18±20 mm Hg ( P =0.01) and 12%±14%, and drop in diastolic BP were 6.5±10 mm Hg ( P =0.05) and 7%±11%, respectively. The mean and percentage drop in HR were 2±0.6 bpm ( P =0.48) and 2%±13%, respectively. None of the subjects experienced any medication-related adverse effects. At 2 hours, the mean and percentage drop in IOP were 5.3±3 mm Hg and 17%±11%, respectively. Conclusion: In the small sample of (ASA I-II) patients studied, preoperative dexmedetomidine produced a significant drop in IOP (33%) within 15 minutes of IV administration in patients with glaucoma that was reversing at 2 hours, with a good safety profile. Abstract : Supplemental Digital Content is available in the text.